High Rate of Repeat Sexually Transmitted Diseases Among Men Who Have Sex With Men in South Africa: A Prospective Cohort Study. Issue 11 (November 2019) - van Liere, Geneviève A.F.S.; Kock, Marleen M.; Radebe, Oscar; Struthers, Helen E.; Morre, Servaas; McIntyre, James A.; Peters, Remco P.H.
Abstract : Abstract: We observed a high rate of incident sexually transmitted diseases within 55 days (median) of follow-up (78% retention) among symptomatic men who have sex with men (n = 78) in South Africa (188 per 100 person-years; 95% confidence interval, 1.2–2.7); 16 newly acquired and 10 with persistent positivity. This highlights the need to strengthen prevention efforts, whereas introduction of diagnostics is urgently warranted. Abstract : There is high incidence of urethral and rectal sexually transmitted diseases among symptomatic South African men who have sex with men, highlighting the need to strengthen sexually transmitted disease prevention and control strategies.